ERROR ANALYSIS OF VERB TENSE IN WRITING ESSAY TEXT - Akmalia Annisa; Shinta Fitri Laoly; Claudia Atlanta Ulfa; Yenni Silvia Br. Gurusinga; Cindy Jessica; Irma Khoirot Daulay (BIP: Jurnal Bahasa Indonesia Prima, 2020)
The purpose of this study is to analyze students 'mistakes in essay writing especially in verbs and to understand the level of students ability to write English essays. This research method is qualitative descriptive. There were 15 students at SMK Mulia Pratama Vocational School that were used as research samples. In research that yielded: the level of student’s ability to write English essays that require mistakes made on verbs is “fair.